Eksplorasi Kebutuhan Perkuliahan Kalkulus pada Kelas Kolaboratif: Apakah Integrasi Virtual Reality Berbasis Etnomatika Diperlukan? - Gunadi, Farid; Isnawan, Muhamad Galang; Rusmayadi, Muh.; Santosa, Farah Heniati; Nurafifah, Luthfiyati; Mulyana, Diki; Alsulami, Naif Mastoor (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2024)
Integral calculus is an important course, but it often becomes a problematic phenomenon for students, even in collaborative learning settings. Various types of research have been conducted to examine this phenomenon, one of which is phenomenology. The purpose of this study is to analyze the experiences of students in collaborative integral calculus courses. The study involved two program chairs, two lecturers, and nineteen prospective mathematics teachers from programs in Indramayu and Mataram, Indonesia. The main instrument in this study was the researcher, supported by additional tools such as program observation sheets, lecturer interview guides, and student questionnaires. The research data were analyzed using thematic analysis. The findings revealed several challenges in the course, such as students' lack of readiness for online learning and visualization, the short duration of discussion videos that were not yet linked to real-world contexts, and unstable internet connections. Although the outcomes of collaborative learning have not surpassed those of conventional methods, there are several advantages, such as students being able to replay discussion videos and gain new peers. This study recommends that collaborative learning should utilize virtual reality based on ethnomathematics, increase the number of discussion videos, and strengthen students' prerequisite knowledge to better meet the needs in integral calculus courses.